Desarrollo curricular y recursos educativos en las bibliotecas escolares - Inmaculada Santos Díaz (Investigaciones Sobre Lectura)
The aim of this study is to evaluate the curricular development and educational resources of the school libraries in Málaga. The provincial coordination of the Educational Local Office has carried out- since the academic course 2008/2009- an annual evaluation focused on five dimensions related to the actions of the Provincial Network of School Libraries. This Network is formed by the public schools of Primary and Secondary Education of the province. This article presents the most relevant results of the evaluation questionnaire for the 2014/2015 academic year in which 430 educational centres participated, offering a comparison according to the educational centre (pre-school, primary school or secondary school) and the school year. In general, there is progress in school libraries due to its normative regulation, the involvement of teachers in charge of libraries in collegiate bodies, the use of digital tools and social networks. However, there is a need to expand the opening hours of the library, to reinforce the collaboration of teachers who coordinate educational projects and to improve the sections and links of the web portals of libraries. On the one hand, these conclusions are intended to serve as a self-assessment to help school librarians to reflect and identify their strengths and weaknesses. On the other hand, they show the development of the key actions of school libraries, both their progress and their deficiencies, in relation to the standards established at national and international level.